ELASTISITAS PERMINTAAN KONSUMEN RUMAH TANGGA DI PEDESAAN SENTRA PRODUKSI TERHADAP HARGA BERBAGAI JENIS PRODUK KOPI OLAHAN - Alamsyah, Idham (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2009)
Research conducted in the village Sipatuhu, a rural coffee production center in the District Court District Letter Ogan Komering Ulu Selatan. Using the method of survey sampling technique with random fluke of 20 renponden household. Collecting data is done in June 2005 to data 2004 and 2005. The purpose of research analyzing the demand elasticity of the price difference because of the option type of processed coffee products, and analyze the elasticity of demand because of price changes in coffee production. Results of research indicate: 1). Demand for certain types of price differences in products processed coffee elastic. This means the option price becomes the basis of considerations in the purchase. In addition to the options on the price, consumers also purchase decisions in the womb pengaruhi by element product, is indicated by not elastisnya particular type of product that is mixed ginseng coffee and coffee mixed pinang. 2). Consumer demand for price changes in processed coffee prices in the village center of production is not elastic, This is because coffee is a need for primary products remain so demand, the price is not affected and is not replaced by another product substitution.